Implementing Game-Based Learning Using Wordwall in Teaching English Vocabulary for Junior School Students - Listiana Uswatun Khasanah; Praditya Putri Utami; Maya Rahmawati (FKIP - Universitas Riau, 2026)
This study explores how game-based learning (GBL) using Wordwall is carried out in teaching English vocabulary to junior high school students. This study aims to describe the classroom application of GBL and examine students’ responses throughout the learning activities. This study used a qualitative case study design and involved eighth-grade students who took part in three sessions of game-based learning. The data were collected through classroom observations and semi-structured interviews at a junior high school in Jakarta. The collected data were analyzed using thematic analysis to identify patterns related to the implementation and students’ responses. The findings show that using GBL created a more engaging and interactive classroom atmosphere. Students participated actively and felt more motivated, especially when learning through games and competitive tasks. They also reported that the games made it easier for them to understand and remember new vocabulary. This study concludes that implementing game-based learning using Wordwall effectively supports students’ vocabulary development while also encouraging motivation and positive attitudes toward learning English.